Enhancement of current peak multiplicity related to cuprous oxide electroreduction and transient copper activation in alkaline solution - Martins, María Elisa (1984)
Anodic films formed on Cu electrodes immersed in 0.1 M NaOH in the Cu/Cu(I) potential range were subjected to combined triangular potential sweeps and then immediately electroreduced to confirm the multiplicity of the species anodically formed and to investigate the roughening and sintering processes at the metal surface. These two processes are tentatively related to the increaee in the cathodic current in the hydrogen evolution potential range, a fact which is apparently due to the electrode surface morphology attained after the potential perturbation programme was applied to the electrode, as deduced from SEM patterns.